Optimal Use of Transient Elastography and Acoustic Radiation Force Impulse to Stage Liver Fibrosis in HIV/HCV‐Coinfected Patients in Clinical Practice. (17th July 2017) - López, Juan José; Pérez‐Àlvarez, Núria; Rodríguez, Raul V.; Jou, Antoni; Carbonell, Pere; Jiménez, José A.; Soldevila, Laura; Tenesa, Montserrat; Tor, Jordi; Clotet, Bonaventura; Bechini, Jordi; Tural, Cristina
Abstract : Objectives: Liver fibrosis (LF) is crucial for the individualized management of patients with hepatitis C virus (HCV). We evaluated the concordance between two noninvasive methods for staging LF, transient elastography (TE) and acoustic radiation force impulse (ARFI), in patients coinfected with human immunodeficiency virus and HCV. We propose an algorithm for optimal use of both techniques in routine clinical practice. Methods: A total of 89 human immunodeficiency virus/HCV‐coinfected patients underwent TE and ARFI on the same day. The kappa index was used to assess concordance between the techniques. An algorithm combining ARFI and TE was proposed based on the independent factors associated with a kappa index greater than or equal to 0.70, obtained from a multiple regression analysis. We performed a cost‐effectiveness analysis. The study was approved by our institutional review board and all patients signed the informed consent. Results: Concordance between TE and ARFI for F2, F3, and F4 was 0.55, 0.59, and 0.69, respectively. Ultrasound normal spleen size (odds ratio [OR], 0.20; 95% confidence interval [CI], 0.05–0.91) and high viral load (OR, 0.36; 95% CI, 0.17–0.77) reduced the probability of agreement between TE and ARFI, whereas ultrasound normal left liver lobe size (OR, 3.32; 95% CI, 1.21–9.10) increased this probability. The algorithm revealed that LF was adequately assessed in 74.16%, with 25.84% of patients misclassified. The incremental cost‐effectiveness ratio of TE compared with ARFI to increase concordance by 1% was €8.86. Conclusions: Concordance between TE and ARFI was moderate. In the algorithm we proposed, ARFI was cost‐effective as a first technique for the staging of LF in the study population.